Molecular Dynamics Simulation of Water/BHDC Cationic Reverse Micelles. Structural Characterization, Dynamical Properties, and Influence of Solvent on Intermicellar Interactions - Agazzi, Federico Martin (2014)
We report results obtained from molecular dynamics (MD) experiments of benzylhexadecyldimethylammonium chloride (BHDC) cationic reverse micelles (RMs). In particular we analyzed equilibrium and dynamical characteristics of water/BHDC RMs in pure benzene, at two different water/BHDC ratios (W0 = 5 and W0 = 10). The RMs appear as elliptical aggregates with eccentricities close to ∼0.9. Analysis of the different spatial correlations reveals three different spatial domains in the RMs: a water inner pool, the surfactant interface, and the external solvent. The calculated accessible surface areas for the aqueous inner cores suggest a strong penetration of solvent molecules within the micellar interface domains. Comparison between the density profiles of both RMs shows an increment of the broadness in the distributions of all species at the interface, along with an increasing overlap between the tail segments of the surfactant and benzene molecules as one considers larger micelles. For the dynamical side, the rotational characteristic time scale for the confined water was found to be 1 order of magnitude larger than that of the bulk water. A similar effect was also observed for hydrogen bond dynamics. Both retardation effects diminish with the size of the aggregate. To the estimate the influence of the external solvent on the intermicellar interactions, free energy profiles for the coalescence process between RMs of similar size in pure benzene and in a n-heptane/benzene mixture were also investigated. The results indicate that the association process is facilitated by the presence of n-heptane in the external nonpolar phase. Comparison with previous theoretical and experimental results is also carried out.